Otwarta kultura organizacyjna warunkiem rozwoju zdolności uczenia się współczesnych przedsiębiorstw - Zgrzywa-Ziemak, Anna (Open corporate culture as a condition of the development of contemporary enterprises' learning capability, 2005)
The paper provides the results of empirical research into the share of corporate culture in the development of the enterprises' learning capability. Especially the conception of 'open corporate culture' was discussed. The importance of 'organizational continuity' development was indicated.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 692-699